Militant jihadism: today and tomorrow - Pektaş, Şerafettin; Leman, Johan (Current issues in Islam, 2019)
Jihadist militants keep being a global threat. Many observers suggest that a transformation is likely to happen in their organisation, operation, mobilisation, and recruitment strategies, particularly after the territorial decline of the Caliphate of the Islamic State. This volume explores different aspects of the future trajectories of militant jihadism and the prospective transformation of this movement in and around Europe. The authors analyse the changing jihadist landscape and networks, and the societal challenges posed by both returned foreign terrorist fighters and those who have not returned to their countries of origin. Other topics of discussion are cyber jihadism, jihadist financing, women's position in and relevance for contemporary jihadism, the role of prisons in relation to radicalisation and militancy, and the changing theological dynamics. Based on recent empirical research, 'Militant Jihadism' offers a solid scholarly contribution to various disciplines that study violence, terrorism, security, and extremism